2006
DOI: 10.1592/phco.26.5.619
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial to Improve Laboratory Safety Monitoring of Ongoing Drug Therapy in Ambulatory Patients

Abstract: A computerized tool plus collaboration of health care professionals effectively increased the number of patients who received laboratory safety monitoring of drug therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 19 publications
0
41
0
Order By: Relevance
“…4,[9][10][11][12] In a randomized intervention trial conducted during 2003 at one of the sites that participated in the current study, 15% of patients who were prescribed amiodarone and who received thyroid and/or aminotransferase laboratory testing as a result of the study intervention had abnormal test results. 33 There is the possibility that some patients were misclassified as continuing on amiodarone therapy. On the basis of the study definition of continuing dispensings, patients with as few as 2 dispensings of amiodarone in the 180-day dispensing period were included (Table 4).…”
Section: Accuracy Of Administrative Claims Data In Comparison To the mentioning
confidence: 99%
“…4,[9][10][11][12] In a randomized intervention trial conducted during 2003 at one of the sites that participated in the current study, 15% of patients who were prescribed amiodarone and who received thyroid and/or aminotransferase laboratory testing as a result of the study intervention had abnormal test results. 33 There is the possibility that some patients were misclassified as continuing on amiodarone therapy. On the basis of the study definition of continuing dispensings, patients with as few as 2 dispensings of amiodarone in the 180-day dispensing period were included (Table 4).…”
Section: Accuracy Of Administrative Claims Data In Comparison To the mentioning
confidence: 99%
“…In addition to the sources for the Royal College of General Practitioners (RCGP) indicators, [3][4][5] a number of new key papers were found that were previously unknown to the authors (Table 1). [6][7][8][9][10][11]17 Over 600 prescribing indicators were reviewed against the inclusion and exclusion criteria, and against attributes of good indicators, including importance, validity, and feasibility of data collection using electronic health records. Exclusion criteria 1.…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] Most of the indicator sets developed specifically for primary care originated in the UK. [12][13][14][15][16][17] Other methods of analysing prescribing also exist, for example, prescribing analysis and cost tabulation (PACT) data and the Medication Appropriateness Index (MAI).…”
Section: Introductionmentioning
confidence: 99%
“…3 Collaboration between pharmacists and physicians, in conjunction with an electronic alerting tool, increased the number of ambulatory patients receiving appropriate baseline laboratory monitoring for medications. 4 This expansion of pharmacy services has also been documented to improve patient outcomes. Pharmacist-managed aminoglycoside, vancomycin, and antiepileptic therapy has been associated with significantly improved economic and clinical outcomes in Medicare patients.…”
Section: Résultatsmentioning
confidence: 99%